A Review of Computer-Assisted Instruction for Students With Visual Impairment. (November 2022) - Tuttle, Michael; Carter, Erik W.
Computer-assisted instruction (CAI) is a critical tool for accessing information and instruction among students with visual impairment (VI). This systematic review examined eight CAI intervention studies implemented with 92 U.S. school-age children with VI. The interventions were implemented with a diverse group of students across a variety of school types (e.g., neighborhood schools, schools for the blind), grade levels, and content areas (e.g., math, reading). Although some findings were promising, the effects of CAI were inconsistent across studies. This review highlights the need for (a) additional high-quality intervention evaluations, (b) more information on the social validity of CAI interventions, and (c) evaluations of CAI among students with a wider range of needs. Implications for practice and research aimed at enhancing the use of CAI are addressed.